Analysis of the Physical Conditions of Men's Futsal Athletes at the Kenanga Futsal Club in Bengkulu City - Agusril, Agusril; Lesmana, S. A.; Wibowo, T. P. (Journal Of Dehasen Educational Review, 2023)
Achievement sports are sports that foster and develop athletes in a planned, tiered and sustainable manner through competence to achieve high achievements with the support of sports science and technology. In accordance with the definition of achievement sport mentioned above, achievement sport is a sport of fostering and developing potential in a person which is carried out in a planned, tiered and competent manner with the aim of achieving high achievements. In carrying out sports activities a person must have a good physical condition so that he is able to carry out the sports activities he does without experiencing excessive fatigue, conversely if a person has a poor physical condition let alone bad then a person will have difficulty in carrying out these sports activities causing excessive fatigue. Achievement sports that are developing at this time range from individual sports to group sports or team sports. Through this futsal sport, teenagers get many benefits, especially in terms of good physical, mental and social growth. The purpose of people playing futsal is basically the same, namely to have fun, get physical fitness and to achieve optimal performance. This research is a descriptive type of research, which aims to find out the problems that occur in the men's Futsal athletes at the Bengkulu Kenanga Club, how the level of physical condition of futsal athletes decreases. Based on the results of the research above, it can be concluded that during training, many athletes are lazy. Because during practice the athletes feel they are too portioned during practice. Even though the purpose of physical exercise is to build strength, agility and balance. And there are also many factors that make the physical condition of male futsal athletes decline, including the effects of smoking, frequent staying up late, lack of regular exercise, these are some of the things that make athletes very weak.